Development of endurance in physical education lessons with the use of outdoor games (Bangladesh Journal of Medical Science, 2024)
Background: Endurance is of great importance for the growth and development of the body of schoolchildren, and is also the foundation for the development of other physical qualities. The low level of endurance of modern schoolchildren requires the search for new ways to improve the system of physical education.The aim of the study: To increase the level of endurance development in schoolchildren using outdoor games in physical education classes at school.Study design: Pedagogical experiment.Research methods: The research was carried out on the basis of secondary school number 30 in the city of Kirov, Russian Federation. The experiment was attended by 3rd grade students aged 9-10 years. The study took place from September 6 to December 26, 2022 during physical education lessons 2 times a week for 45 minutes each lesson. In total, 2 groups of 25 people were formed. Classes in the control group were conducted according to the standard program, and in the experimental group, outdoor games were additionally conducted at each lesson for 6-7 minutes. Tests that were used to determine endurance: flexion and extension of the arms while lying on the floor, running 30 meters, Vis bent arms, lifting the trunk from the supine position, running 1000 m.Results: After the end of the pedagogical experiment, the indicators of school children in both groups became higher. In the control group, the indicators were reliable only in the test for flexion and extension of the arms while lying on the floor. In the experimental group, by the end of the study, the results in all 5 tests showed a significant and reliable result. Flexion and extension of the arms in the prone position from 15,6±0,76 to 19,7±0,76 (p< 0.05); Running 30 meters from 6,25±0,08 to 5,99±0,08 (p< 0.05); Vis bent arms from 21,90±0,97 to 27,10±0,97 (p< 0.05); Lifting the trunk from the supine position from 22,40±0,87 to 28,10±0,76 (p< 0.05); running 1000 m from 337,7±8,01 to 311,9±3,9 (p< 0.05).Conclusion: If outdoor games are used in physical education lessons at school when working with children 9-10 years old, then the indicators of different types of endurance will significantly improve.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 254-261